Case Study: UAV Implementation in Mapping and Site Layout Design - Muhammad Fadhillah Al Hafiz Mohamad Alif,; Dafinah Insyirah Sahar,; Fikri Ibrahim, Nurul Aimi; Masiri Kaamin, (Multidisciplinary Applied Research and Innovation, 2025)
Maps are graphical tools that show the features of a specific area, be it a city, country, or continent. The distribution of objects on Earth, including the precise locations of homes and streets in a metropolitan town, can also be seen on maps. The suggested UAV system was designed to carry out surveying tasks in civil engineering applications with success. Typically, GPS is used for mapping purposes. One of the drawbacks is that it is time-consuming and fails to produce current and actual results. So, using the UAV photogrammetry approach provides an alternative solution to this issue. In order to support development planning work the UAV will generate orthophoto images, orthophoto maps, and site layout designs. Unmanned Aerial Systems (UASs) can be useful in pre-construction applications such as site planning and surveying.